The significance of foreign military bases as instruments of spheres of influence - Klin, Tomasz (Array, 2020)
The category of the sphere of influence can explain some contemporary international processes. To define that category, however, much stress is laid on great powers’ exclusivity within their spheres of influence. The author takes into consideration the thesis of the aforementioned exclusivity’s erosion. Because foreign military bases are essential instruments of spheres of influence due to their strong impact on security policy, it is worth investigating their presence in this context. Specifically, the author carries out an in-depth study of military bases of more than one major power in one host country. Further, the article discusses the extent to which the gradual erosion of exclusivity undermines the significance of spheres of influence as such. In conclusion, the author states that the case of Djibouti undermines the idea of great power exclusivity. Yet, other cases do not provide sufficient evidence on such deep transformation because of either limited periods of bases’ existence or great power cooperative attitudes.